Penser et reconstruire sa sexualité après une tumeur testiculaire - Clément Méric (Anthropologie & Santé)
In the past several decades there have been significant breakthroughs in oncology. The treatment of a testicular tumor (the most common cancer in young men) is quite a good example : five years after its diagnosis, the survival rate is equal to 95 %. On the other hand, its repercussions are not minor : almost systematic ablation of the substantially affected testicle, a more or less temporary decrease of libido and fertility or possible problems of ejaculation. While, for the most part, the pathology is no longer life-threatening, patients find themselves wondering about their future possibilities, capacities, and/or limits in different areas of their social lives. The precise aim here is to examine the perceptions of the potential implications of the pathology and its treatments in this field and the possible coping strategies implemented.